2023
DOI: 10.30518/jav.1324997
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Analysis of Society's Perspective on Urban Air Mobility

Ertan ÇINAR,
Arif TUNCAL

Abstract: Urban Air Mobility (UAM) is an innovative concept that offers a distinct solution for dense urban transportation through the use of electric vertical take-off and landing (eVTOL) aircraft and unmanned aerial vehicles (UAVs), despite not being the first technological development in transportation. This study aims to understand society's perspective on this innovative concept by analysing its benefits and challenges. A total of 518 individuals living in Ankara and Istanbul, which are the provinces with the highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Previous studies have revealed that public acceptance of such aerial vehicles can be influenced by public knowledge, awareness, and interactions with UAVs (Melo et al, 2023;Tan et al, 2021). In today's urban environments, there is a lack of information about the use of UAVs equipped with advanced autonomous systems within the scope of UAM (Çınar & Tuncal, 2023;Wang, Mutzner, & Blanchet, 2023). A report published in Australia also supports this view, indicating a neutral attitude stemming from a lack of knowledge about UAV technology (Clothier et al, 2015).…”
Section: Introductıonmentioning
confidence: 99%
“…Previous studies have revealed that public acceptance of such aerial vehicles can be influenced by public knowledge, awareness, and interactions with UAVs (Melo et al, 2023;Tan et al, 2021). In today's urban environments, there is a lack of information about the use of UAVs equipped with advanced autonomous systems within the scope of UAM (Çınar & Tuncal, 2023;Wang, Mutzner, & Blanchet, 2023). A report published in Australia also supports this view, indicating a neutral attitude stemming from a lack of knowledge about UAV technology (Clothier et al, 2015).…”
Section: Introductıonmentioning
confidence: 99%